PENGARUH KECEPATAN PEMAKANAN TERHADAP KEKASARAN PERMUKAAN BENDA KERJA PADA MESIN BUBUT KENT USA RML-1640T - Yosua Li; Romels Lumintang; Rudy Poeng (JURNAL POROS TEKNIK MESIN UNSRAT, 2023)
In the turning process, surface roughness is one of the important properties of the surface of an object because it determines whether or not the machine elements function properly. This is an obstacle in the industry, especially in manufacturing because it must be able to produce products with good surface roughness quality. Under these conditions, it is necessary to choose the right machining parameters. Some of the machining parameters that affect the quality of surface roughness are the main cutting angle and the feeding motion of the workpiece or feeding. Therefore, surface roughness is a measure of the accuracy and surface quality of a manufactured industrial product. The purpose of this study was to analyze the effect of feeding speed on the workpiece surface roughness in the KENT USA RML-1640T lathe process. To obtain the research results, it is necessary to test the lathe by varying the rotation by using a feed motion and a fixed depth of cut and the same test object material. The results of the analysis obtained from this study indicate that the feeding speed increases, the surface roughness increases. From the results of simple linear regression analysis, the regression line equation is obtained y ́ =2.839+0.030x which predicts that for every 1 mm/min increase in infeed speed, the surface roughness on the lathe for infeed speeds of 114 to 380 mmm/r will increase by 0.030 μm. And from the significant test results, it was found that feeding speed had a significant effect on the surface roughness of the turning process.. Keywords: Feeding Speed, Surface Roughness, Lathe Process